Pengaruh Pelatihan, Pembagian Tugas, Keterampilan Kerja Dan Pengembangan Karier Terhadap Prestasi Kerja Pegawai Satuan Polisi Pamong Praja Kabupaten Empat Lawang - Hurliansyah, Hurliansyah; Alista, Nisma Aprini; Alista, Delvina Yulanda (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi, 2025)
The purpose of this study was to determine and analyze the effect of training, task allocation, work skills, and career development, individually and collectively, on the work performance of employees at the Empat Lawang Regency Civil Service Police Unit. The research method used in this study was quantitative, using a questionnaire distributed to respondents. Data quality was tested using validity, reliability, and normality tests. The analysis used descriptive and inferential analyses using statistical calculations using multiple regression formulas, partial and simultaneous tests, and the coefficient of determination. The results showed that training significantly influenced the work performance of employees at the Empat Lawang Regency Civil Service Police Unit. Task allocation significantly influenced the work performance of employees at the Empat Lawang Regency Civil Service Police Unit. Work skills significantly influenced the work performance of employees at the Empat Lawang Regency Civil Service Police Unit. Career development significantly influenced the work performance of employees at the Empat Lawang Regency Civil Service Police Unit. Training, task allocation, work skills, and career development significantly influenced the work performance of employees at the Empat Lawang Regency Civil Service Police Unit.